HUBUNGAN ANTARA CAREGIVER BURDEN DENGAN SUBJECTIVE WELL-BEING PADA IBU GENERASI SANDWICH - Indira Khairunnisa; Nurul Hartini (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2022)
Caring and providing financial support for two generations in one family is inseparable from declining psychological aspects, one of which is subjective well-being that affected from caregiver burden. It is important for sandwich generation who bear multiple demands, to maintain their subjective well-being in a good quality . Pearson’s correlation analysis was conducted in 81 sandwich generation mothers that leads to result of a significant negative correlation between caregiver burden and subjective well-being (r= -0,539; p < 0,05). This result explains that if the level of caregiver burden is increased, the it decreases the subjective well-being level.